Novel Pulmonary Delivery of Antiviral Drugs for Treating COVID-19 in Patients with Parkinson’s Disease - Islam, Nazrul; Rahman, Shafiqur (Current Drug Delivery, 2022)
The COVID-19 pandemic has caused a significant burden on public health worldwide. Currently, there are limited medications for the treatment of COVID-19 in patients with Parkinson’s disorder (PD). Several antiviral drugs and other pharmacotherapies have shown promising results and are used by various delivery methods. Among the antiviral drugs, amantadine alone was reported to provide therapeutic benefit against COVID-19 in patients with PD. Here, we propose novel strategies for pulmonary drug delivery technology of antiviral drug, amantadine. As such pulmonary delivery of this drug or in combination with the additional antiviral drugs could be a more effective strategy for the treatment of COVID-19-related complications in patients with PD. Furthermore, the important benefits and limitations of this novel delivery technology will be discussed.
Keywords: lung infections